Inter-relationships among traits and path analysis for yield components of cassava: a search for storage root yield indicators - Ntawuruhunga, Pheneas; Rubaihayo, P.; Whyte, J.; Dixon, A.; Osiru, D. (African Journals Online, 2001)
Research aimed at selecting varieties of cassava (Manihot esculenta Crantz) with potential for high storage root yields through identification of stable yield components that can be used as selection criteria was carried out at three locations of different altitudes in Uganda. Multiple regression and simple phenotypic correlation coefficients revealed that storage root number and storage root weight were important components in storage root yield across locations. The path analysis identified leaf area, storage root number, storage root girth and storage root weight as the main yield components with root number (0.53) and storage root weight (0.45) having the highest values of direct path coefficient. Probably due to environmental influence, only 43% of the total variation of the storage root yield relationship was explained by the path coefficient analysis.